Space travel : a technological frontier - De Old, Alan R.; Judge, Joseph W.; Judge, Teri-Lynn. (Worcester, MA : Davis Publications, 1989)
Describes various types of space vehicles such as the Space Station, Manned Maneuvering and Orbital Maneuvering Vehicles, space shuttles, areospace planes, and launch vehicles.
Includes index.
Keywords: Space vehicles; Manned space flight; Space flight; Space vehicles; spacecraft; Exploration of outer space; Manned space flight; Space vehicles; Outer space -- Exploration; Outer space